Pemikiran Sir Sayyid Ahmad Khan “Pembaharuan di India” Relevansinya dengan Ideologi Islam Puritan, Moderat dan Sinkretisme dalam Masyarakat - Fuad Noorzeha (Program Studi Filsafat Agama Hindu IAHN Gde Pudja Mataram, 2019)
As a cultural movement, globalization has presented the differences that tear down the totality and unity of value and belief. Global culture is characterized by the integration of local culture into the global order. Accordingly, various foreign cultural value become the bases of formation of sub culture that stands alone with the freedom of expression. As a cultural movement, it brings the different that undermine the totality and the unity of value and religion belief. This climate conducive to these different ways of life and then spawns a widespread individualization process, which turns man away from the general context. This massive shift can be seen in the so called “privatization of religion”, the process of individualization in the appreciation and religious practices. Revitalization of religion is needed to restore the basic values of religion that have been secularized. Religion must come back as a legitimate sovereign social values and piety. This sovereignty of religion should be structured as a strategy for revitalizing religion in the lives of individual piety personally and socially. However, the sovereignty of religion should give a wide freedom for individuals to perform the fuction of religion in accordance with the present context.